Use and perceptions on reusable and non-reusable menstrual products in Spain: A mixed-methods study - Medina-Perucha, Laura; López-Jiménez, Tomàs; Holst, Anna Sofie; Jacques-Aviñó, Constanza; Munrós-Feliu, Jordina; Martínez-Bueno, Cristina; Valls-Llobet, Carme; Pinzón Sanabria, Diana; Vicente-Hernández, Mª Mercedes; Berenguera, Anna (PLOS ONE, 2022)
Background Menstrual products are necessary goods for women and people who menstruate to manage menstruation. Understanding the use and perceptions of menstrual products is key to promote menstrual equity and menstrual health. This study aimed at assessing the use and perceptions on menstrual products among women and people who menstruate aged 18–55 in Spain. Methods A mixed-methods study was conducted, including a cross-sectional study (N = 22,823), and a qualitative study (N = 34). Results Participants used a combination of products. Non-reusable products were the most used, while over half used reusable products. Usage changed when data were stratified by age, gender identification, completed education, country of birth and experiencing financial issues. It also varied between trans and cis participants. Menstrual products’ use also shifted based on experiences of menstrual poverty and access to information and products. Overall, reusable products were perceived to be more acceptable than non-reusable. Barriers to use the menstrual cup were also identified, including experiences of menstrual inequity (e.g., menstrual poverty, lack of access to information or menstrual management facilities). Conclusion Perceptions and choices of menstrual products need to be acknowledged, especially when designing and implementing menstrual policies to address menstrual inequity and menstrual health.